2021
DOI: 10.1186/s12951-021-00787-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-carbon dots and aptamer based signal amplification ratiometric fluorescence probe for protein tyrosine kinase 7 detection

Abstract: Background Protein tyrosine kinase 7 (PTK 7) is a membrane receptor, which can be found in various kinds of cancers. In view of this, detection of PTK 7 in the peripheral circulation would be an effective way for the early diagnosis of cancer. Results In this work, a multi-carbon dots and aptamer-based signal amplification ratiometric fluorescence probe was developed. The fluorescence of the aptamer-modified y-CDs and b-CDs were respectively chosen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Figure 2 d (upper panel) shows the normalized absorption and emission spectra of a series of CPNs without PtOEP. The absorption spectra of CPNs decorated with aptamers show increased absorption around 255–260 nm, which is associated to the presence of aptamers [ 34 , 35 ]. The shape and intensity of emission spectra is identical for all samples.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 d (upper panel) shows the normalized absorption and emission spectra of a series of CPNs without PtOEP. The absorption spectra of CPNs decorated with aptamers show increased absorption around 255–260 nm, which is associated to the presence of aptamers [ 34 , 35 ]. The shape and intensity of emission spectra is identical for all samples.…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al, designed a fluorescent probe for detecting protein tyrosine kinase 7 in the peripheral circulation using multi-carbon dots and an aptamer-based signal amplification ratiometric. As a result, its presence in the peripheral circulation might help in cancer diagnosis (Ma et al, 2021a).…”
Section: Applications Of Quantum Dots In Cancer Treatment Early Diagnosis Of Cancer By Quantum Dotsmentioning
confidence: 99%
“…However, and a variety of factors can in uence measurement quality, including probe concentration, photosource and experimental conditions [8]. It has also been reported that some ratiometric uorescent probes consist of two or more uorescent materials [9][10][11][12]. In contrast to the conventional uorescence method that utilizes a single uorophore, ratiometric uorescence determination method consisted of multiple uorophores offers increased selectivity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%